Gross Hydronephrosis Secondary to Pelviureteric junction Structure, Complicated with Caliceal Rupture - Assyifaa Nik Mazian; Siti Soraya Ab Rahman (Journal of Clinical Images and Medical Case Reports, 2024)
Non-Indexed Publication